Evaluation of potential role of catharanthus roseus and acanthus ilicifolius in the prevention of azoxymethane-induced aberrant crypt foci in rat's colon / Amel Abdullah Almagrami - Almagrami, Amel Abdullah (2013)
Catharanthus roseus extract is traditionally used to treat different diseases including cancer in Southeast Asia. Acanthus ilicifolius, is a mangrove medicinal plant, and is widely used by the local inhabitants of the Sundarbans (India) to treat a variety of diseases. The aim of current research is to assess the chemoprotective outcomes of ethanolic extracts of C. roseus and A. ilicifolius against azoxymethane (AOM) induced colonic aberrant crypt foci (ACF) in rats. The bioactivities of the crude ethanol extracts of C. roseus and A. ilicifolius were investigated in both of their in vitro antioxidant and in vivo oral toxicity tests. Antioxidant activity was evaluated by different assays, including: 2, 2-diphenlyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), total phenolic content (TPC) and total flavonoids content (TFC) assays. Five groups of rats, normal control group were given subcutaneous injection of normal saline, once weekly for 2 weeks. The AOM control group, reference group and treatment groups were given subcutaneous injection of AOM, 15 mg/kg body weight, once weekly for 2 weeks each. Normal and AOM control groups continued on 10% Tween 20 feeding for 8 weeks. Reference group continued on 35 mg/kg of 5-Fluorouracil intraperitoneal injection once weekly for 8 weeks, and treatment groups continued on 250 and 500 mg/kg C. roseus and A. ilicifolius extracts feeding for 8 weeks respectively. After 60 days treatment, all rats were sacrificed. Colons were evaluated grossly, histopathology and immunohistochemistry staining for ACF. Also body weight, biochemical parameters, catalase (CAT), superoxide dismutase (SOD) activities and lipid peroxidation (MDA) level in the colon homogenates were tested. Gene expressions also were studied for p53, Bax and Bcl2 by real time PCR. In addition, the crude extracts of C. roseus and A. ilicifolius and their isolated fractions were investigated against HT29 and (CCD841) human cell line cell line, and the percentage of inhibition by using MTT assay was assessed. Our results revealed that, extracts of C. roseus and A. ilicifolius exhibited high free radical scavenging activity at the same time, showed high total phenolic and flavonoids contents. Acute toxicity test could not demonstrate any morbidity as well as mortality. Rats treated with C. roseus and A. ilicifolius showed significantly decreased total colonic ACF formation by 61 % to 65 % and 53 % to 65 % respectively when compared with AOM control group and they were effectively comparable to that of 5-Fluorouracil, a standard cemoprotective agent. Histopathological study confirmed the result. In immunohistochemical staining, proliferating nuclear cell antigen (PCNA) positive cells were significantly higher in AOM control group than C. roseus and A. ilicifolius-treated groups. C .roseus showed significant increase in total protein, albumin, hemoglobin, white blood cell, SOD and CAT, and significant decrease in MDA, LDH and urea when contrasted with AOM control group. While A. ilicifolius showed significant increase in total protein, albumin, Hb, SOD and CAT, and significant decreased in MDA and urea when compared with AOM control group. RT-PCR showed that C. roseus and A. ilicifolius caused change in regulation of gene expression of p53, anti-apoptotic protein Bcl-2 and pro-apoptotic protein Bax and inverting the Bcl-2/Bax ratio to <1. Moreover, the results observed from the MTT assay showed that C. roseus and A. ilicifolius plants extract stimulated the normal cell line (CCD841) proliferation in vitro in a dose-dependent manner, at the same time both extracts have remarkable activity against cancer cell line (HT29). The active constituents of the fractions that are proved to have chemoprotective activity in C. roseus are vindoline, vindolidine and ajmalicine while in A. ilicifolius is stigmasterol. The results of the current study showed that C. roseus and A. ilicifolius may be an effective herbal and efficient remedial for chemical-induced against cancer in rats colon.